Geometry Based Efficient Routing Protocol In Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Network (WSN) has gained tremendous research attention recently due to their extensive applications. As sensornodes being battery operated, many researchers have made attempts to prolong the lifespan of the WSN by reducing the-per node energyconsumption and efficiently utilizing the sensor nodes. Since the sensors operate on battery of limited power, it is a great challenging aim todesign an energy efficient routing protocol, which can minimize the delay while offering high-energy efficiency and long span of networklifetime. This is the survey on different deployment schemes on irregular geographical target area, we propose to include the concept ofvoronoi diagram based approach in WSNs, to provide a way of dividing an irregular geographical area into a number of regular regions. Inthis regions, we deployed sensor nodes, among all these nodes CH(cluster head) is selected based on residual energy level of sensor nodes ina cluster. Then fused data of CH will be transmitted to sink node through multihop routing.